Features of the course of myocardial infarction in the elderly - Kamilya Kedelbaeva; Salim Berkinbaev; Gulnar Dzhunusbekova; Meyramgul Tundybaeva; Aizhan Kubeyeva; Darya Utebaliyeva (National Scientific Medical Center, 2021)
Cardiovascular disease is a major contributor to morbidity, mortality and quality of life in people aged 60 and over. However, this age group of patients was not sufficiently included in large studies, in this regard, the management of elderly patients is an urgent problem in modern medicine. The purpose of this review is to analyze of literature data on the characteristics comorbid pathology and senile asthenia as a predictor of unfavorable course and outcomes of acute myocardial infarction in patients 60 years of age and older.  To analyze the literature, we searched for information on this issue in PubMed / MEDLINE, PMC, Web of Science, Scopus, The Сocrane Library. Recent research data show that there are plenty of risk factors for worsening the course of AMI in patients aged 60 and over. The most important of them are considered to be high comorbidity, multivessel lesion of several pools, the presence of senile asthenia. All together lead to difficulties in diagnosing myocardial infarction, to forced polypharmacy and in some cases refraining from early invasive strategy, which worsens the course of the disease, increases the duration of hospital treatment, leads to frequent complications, thereby affects the prognosis of the disease and leads to the development of early disability in patients 60 years of age and older In the vast majority of elderly patients, the development of acute myocardial infarction occurs against the background of a high prevalence of comorbid pathology, which in turn accelerates the development of senile asthenia and its progression.